Asesmen Otentik sebagai Pendukung Desain Instruksional Jaringan Komputer Berstrategi Blended-Learning dengan Pendekatan Konstruktivistik - Sugihartini, Nyoman; Agustini, Ketut (Journal of Education Reseach and Evaluation, 2017)
This study aimed to develop instructional design of computer network courses packed with blanded learning strategy, and presented with constructivist approach of subak concept. The method used in this research is the method of research and development (R & D) using the Instructional Development Models (MPI) steps that adapt the Dick & Carey model. Each Chapter, equipped with an evaluation packed with authentic assessment. The authentic assessments used include: performance assessments, essays, products and portfolios. Based on the analysis of needs and instructional that has been done can be concluded that according to the syllabus used, there are 11 Chapter with twenty-three special instructional purposes computer network lecture material that can be analogy in subak concept. Three chapters have not been successfully analysed: internet protocol material, internetworking and naming protocol and directori.